Processing of Rice Husk into Bleaching Earth Using the Precipitation Method for Adsorption of Colorants in Palm Oil - Fidela Lathifa Haryati; Puspa Prima Andini; Nurul Widji Triana; Susilowati Susilowati; Suprihatin Suprihatin (Universitas Islam Raden Rahmat, Malang, 2025)
Rice husk waste from rice milling in Indonesia contains high silica, making it a promising raw material for adsorbent synthesis. This research contributes to sustainable waste utilization and supports green technology in palm oil refining, providing both environmental and industrial significance. This study focuses on producing Bleaching Earth from rice husk using the precipitation method and applying it to adsorb colorants in used cooking oil. Rice husk ash (RHA) was reacted with sodium hydroxide (NaOH) to form sodium silicate, which was then precipitated using sodium aluminate (NaAlO₂) and hydrochloric acid (HCl) to obtain silica gel. The process variables were the volume of NaAlO₂ solution (15–35 mL) and stirring time (10–50 minutes). The synthesized Bleaching Earth was analyzed for moisture content, pH, chemical composition (XRF), and surface properties (BET). The best Bleaching Earth met the Indonesian National Standard (SNI 136336-2000), with a moisture content of 2.48–6.01%, neutral pH ( 7), and mesoporous structure with pore diameters of 6,49–13.87 nm. The optimal adsorption performance occurred at a pore diameter of 11–12 nm, achieved using 25 mL NaAlO₂ with 50 minutes of stirring or 35 mL NaAlO₂ with 40 minutes of stirring. Application of this BE effectively reduced the color intensity of used cooking oil, producing lighter and clearer oil, confirming rice husk’s potential as an eco-friendly, low-cost source for Bleaching Earth production.